Analysis of Expressions of Heat Shock Protein Genes in Nigerian indigenous Goats exposed to Heat Stress - Tella, Adetunmbi (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
HSP90 and HSP70 genes (markers) were used with 45 genomic deoxyribonucleic acid (DNA) isolated from West African Dwarf goat breeds in Nigeria to determine the expression patterns amongst the heat shock protein genes. Polymorphism information content (PIC) of marker; was determined to ascertain the informativeness of the marker. Fourty five numbers of samples were obtained from WAD goats which were apparently healthy from Osun, Oyo and Kwara State of Nigeria. At the time of collection, the ambient temperature (0°C) and relative humidity (RH) (percent) were also recorded and this revealed that all the sampled animals were heat stressed. Polymerase chain reaction (PCR) was carried out using each marker (heat shock protein gene) , isolated DNA, doublen distilled water and PCR Master Mix. PCR products generated were subjected to polyacrylamide gel electrophoresis on an ABI 3730 DNA Sequencer. DNA bands were scored based on size of ladder with Gene Scan 3.1.2. Bands obtained were designated as alleles and prepared into Excel Worksheet with Microsatellite Analyzer version 4.05 software and allele frequencies were generated. The results revealed allele A and C as major allele by marker SSR1 (HSP90) and marker SSR2 ( HSP70) genes respectively with percentage value of allele A slightly higher than C , effective number of alleles for all loci of SSR1 was lower than the SSR2.. The heighest (Ne1) expected heterozygousity value of 0.40 was revealed by marker 2(HSP 70 gene) as against the lower value of 0.36 revealed by marker 1 (HSP 90 gene) in WAD goats. PIC per gene or marker across populations ranged from 0.55 (HSP90 ) to 0.59 (HSP70) indicating that the markers were informative (PIC â‰¥ 0.50). In conclusion, the two markers (HSP 90 and HSP 70) could therefore be serving as bio-markers for selection and breeding programmes for thermo- tolerance in livestock animals especially WAD goats under thermal stress.